Rancang Bangun Alat Penghitung Buah Kelapa Pada Mesin Pengupas Sabut Kelapa Di Indragiri Hilir - Ervianto, Edy (Universitas Multi Data Palembang, 2024)
Peeling coconut fiber generally still uses traditional equipment and some also use machines. After peeling coconuts, farmers always re-count the coconuts that have been peeled, where farmers often miscalculate the results of coconuts that have been peeled. From this problem, a tool is needed to count coconuts that have been peeled. This tool aims to help peel and count the number of coconuts that have been peeled. This tool will use an infrared sensor as a detector to count coconuts that have been peeled by a coconut fiber peeling machine. In the tool system, an Arduino Uno ATMega328 microcontroller is used to control the counter system and the research results will be displayed on a 16x2 LCD in the form of the number and maximum limit of coconuts that can be detected. The tool is designed to use a 7.4 V battery as the energy source for the tool and a buzzer as an indicator that the coconut passing through the sensor is detected. Farmers can set the limit of coconuts that will be counted by pressing the number on the keypad as desired. In the designed tool, the maximum number of coconuts that can be counted is 3000 coconut.